Obstructive Sleep Apnea (OSA) and Patent Foramen Ovale (PFO), the “Perfect Storm” for a Cryptogenic Stroke? Case Series of Four Patients - Schwarz, Alexandra; Lee, Albert; Gadallah, Nancy E.; Wong, Jessalyn; Gupta, Divya (Frontiers in Stroke, 2022)
We were intrigued by the finding of severe OSA in patients referred to our Sleep Clinic with history of stroke at a relatively young age, in the setting of a PFO. This prompted us to do a literature search to see the association of OSA with stroke in such a patient population. The correlation of PFOs with cryptogenic strokes is well established, as is that of OSA with stroke. However, not many studies have looked at the correlation of OSA and PFO in patients with cryptogenic strokes.